New Methodologies for the Surface Application of Limestone and Gypsum in Different Crop Systems - Borges, Wander Luis Barbosa; Gatto Juliano, Pedro Henrique [UNESP]; Dalto de Souza, Isabela Malaquias [UNESP]; Fuzaro Rodrigues, Letícia Nayara [UNESP]; Hipólito, Jorge Luiz; Andreotti, Marcelo [UNESP] (MDPI, 2022)
To address the problems of soil acidity (pH values below 4.4) in surface and subsurface soil layers and improve soil chemical fertility, this study evaluated three methodologies for surface application of limestone (LS) (ensuring that calcium (Ca)2+ occupied 70%, 60% or 50% of cation exchange capacity (CEC) at a depth of 0.0–0.2 m) and gypsum (GP, phosphogypsum) (ensuring that Ca2+ occupied 60%, 50% or 40% of effective cation exchange capacity (ECEC) at a depth of 0.2–0.4 m). LS and GP were applied in a conventional pasture system (CPS), no-till system (NTS), and agropastoral system (APS) in an Arenic Hapludult in Brazil. Surface application of LS and GP using these three methodologies corrected surface and subsurface acidity and improved soil chemical fertility. Specifically, Ca2+ content increased in the CPS, NTS, and APS at a depth of 0.0–0.2 m and in the CPS and APS at a depth of 0.2–0.4 m; sulfur (S)-SO42− content and Ca2+/ECEC increased in the CPS, NTS, and APS at a depth of 0.2–0.4 m; base saturation (BS) increased and aluminum (Al)3+ content decreased in the NTS and APS at depths of 0.0–0.2 m and 0.2–0.4 m; and pH, magnesium (Mg)2+ content, CEC, Ca2+/CEC, and Mg2+/CEC increased and total acidity decreased in the NTS and APS at a depth of 0.0–0.2 m.
Keywords: agropastoral system; conventional pasture system; no-till system; soil acidity; soil fertility